Investigating the Relationship between Students’ Strategic Thinking Skills and Information Seeking Behavior among Undergraduate Students of Management in University of Tehran - Mohammad Abooyee ardakan; fatemeh ghadyani; Tahereh Alidadi (Journal of Information Technology Management)
This study aims to consider the relationship between undergraduate management students’ strategic thinkingskills and their information seeking behaviors. The statistical population for this study was 400 undergraduate students of management faculty in University of Tehran and the sample size was calculated to be 201 students using Cookran formula. In this study, survey methodology was applied and the data were analyzed using structural equation modeling, Pearson correlation, and multiple regression tests. Based on Pisapia’s model of strategic thinking and ACRL model of information seeking behavior , the results indicated that in among the different dimensions of strategic thinking, reframing thinking  skill (leading to the formation of new values and  getting away from the old clichés) has caused the highest change unit in information seeking behavior.